The Short Textbook of Medical Microbiology - Thapa, Badri (Kathmandu University Medical Journal, 2010)
The Short Textbook of Medical Microbiology (Including Parasitology) By Satish Gupte 10th Edition Price Rs. 632/- Published by Jaypee Brothers Medical Publishers (P.) Ltd. DOI: 10.3126/kumj.v8i2.3579 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 287